Healthy Beauty Value Dalam Keberlangsungan Produk Wardah Di Masa Pandemi - Eva Sulastri; Rahmawaty (LPPM Universitas Pramita Indonesia, 2022)
In addition to being the first and best-selling halal cosmetic in the market, Wardah also has the tagline